2018
DOI: 10.1007/s00167-018-4865-y
|View full text |Cite
|
Sign up to set email alerts
|

2018 International Olympic Committee consensus statement on prevention, diagnosis and management of paediatric anterior cruciate ligament (ACL) injuries

Abstract: In October 2017, the International Olympic Committee hosted an international expert group of physiotherapists and orthopaedic surgeons who specialise in treating and researching paediatric anterior cruciate ligament (ACL) injuries. Representatives from the American Orthopaedic Society for Sports Medicine, European Paediatric Orthopaedic Society, European Society for Sports Traumatology, Knee Surgery and Arthroscopy, International Society of Arthroscopy Knee Surgery and Orthopaedic Sports Medicine, Pediatric Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 149 publications
(197 reference statements)
0
86
0
Order By: Relevance
“…41 Likewise, the KOOS-Child has demonstrated good psychometric properties in 7- to 16-year-old children with knee disorders. 69 In a consensus statement by Ardern et al, 2 the Pedi-IKDC and KOOS-Child were suggested as appropriate PROMs for children with ACL injury. In our review, only 5 studies used the Pedi-IKDC, and 1 study used the KOOS-Child.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…41 Likewise, the KOOS-Child has demonstrated good psychometric properties in 7- to 16-year-old children with knee disorders. 69 In a consensus statement by Ardern et al, 2 the Pedi-IKDC and KOOS-Child were suggested as appropriate PROMs for children with ACL injury. In our review, only 5 studies used the Pedi-IKDC, and 1 study used the KOOS-Child.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the recent consensus statement highlights the need for standardized, pediatric-specific PROMs to be applied in future studies evaluating the treatment of children and adolescents after ACL injury. 2 To our knowledge, no studies so far have evaluated the long-term outcomes after pediatric ACL injury, including the risk of developing knee osteoarthritis. Thus, the need for reliable and valid outcome measures that can be applied in both childhood and adulthood seem warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the special requirements of training and competitions, physical fitness is especially important for competitive alpine ski racers, regardless of their age [ 2 ]. Therefore, a comprehensive fitness program starting at a young age is crucial for alpine ski racers to cope with the physical demands of alpine ski racing and minimizing the rate of both traumatic and overuse injuries [ 3 , 4 , 5 ]. In Austria, ski boarding schools are a critical part of the long-term development of youth alpine ski racers.…”
Section: Introductionmentioning
confidence: 99%